How Do Book Trailers Affect The Recipients? Results Of The First Online Experiment In Germany - Schäfer-Hock, Christian; Hartmann, Daniela (Communication Today, 2025)
As far as we know, an experiment on the effect of book trailers has not yet been presented to a broader academic public. Our findings: Book trailers are – compared to blurbs – better able to make clear to the future reader which genre the book they are considering buying belongs to. In our experiment, however, they were not able to increase the interest in reading more strongly, nor did they manage to make a book seem more exciting in the comparison carried out to blurbs.